Marketing and Pricing Risk in Marine Insurance in Sixteenth-Century Antwerp. (21st August 2017) - Puttevils, Jeroen; Deloof, Marc
Abstract : Drawing on a set of insurance contracts brokered in Antwerp in 1562–1563, we demonstrate that by that time Antwerp hosted a sophisticated, large, and international market for marine insurance in which small and large traders could acquire and sell insurance, backed by the intermediation of a large broker, Juan Henriquez who functioned as an open-access institution. Using information from Henriquez's ledgers which was also available to underwriters, we find that insurance premiums reflected the underlying risk and that agents were able to determine the effect of different contract parameters.